Motor Cortex Plasticity during Unilateral Finger Movement with Mirror Visual Feedback - Hatice Kumru; Sergiu Albu; Raul Pelayo; John Rothwell; Eloy Opisso; Daniel Leon; Dolor Soler; Josep Maria Tormos (Neural Plasticity)
Plasticity is one of the most important physiological mechanisms underlying motor recovery from brain lesions. Rehabilitation methods, such as mirror visual feedback therapy, which are based on multisensory integration of motor, cognitive, and perceptual processes, are considered effective methods to induce cortical reorganization. The present study investigated 3 different types of visual feedback (direct, mirrored, and blocked visual feedback: DVF, MVF, and BVF, resp.) on M1 cortex excitability and intracortical inhibition/facilitation at rest and during phasic unimanual motor task in 11 healthy individuals. The excitability of the ipsilateral M1 cortex and the intracortical facilitation increased during motor task performance in the DVF and MVF but not in the BVF condition. In addition, MVF induced cortical disinhibition of the ipsilateral hemisphere to the index finger performing the motor task, which was greater when compared to the BVF and restricted to the homologue first dorsal interosseous muscle. The visual feedback is relevant to M1 cortex excitability modulation but the MVF plays a crucial role in promoting changes in intracortical inhibition in comparison to BVF. Altogether, it can be concluded that a combination of motor training with MVF therapy may induce more robust neuroplastic changes through multisensory integration that is relevant to motor rehabilitation.